Words for the heart a treasury of emotions from classical India - Heim, Maria 1969- (Princeton Oxford Princeton University Press, 2022)
"This anthology offers a guide to classical Indian approaches to emotion"--
Includes bibliographical references and index
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Buddhism -- Psychology; Emotions -- Religious aspects -- Buddhism; Emotions -- Social aspects -- India -- History; Emotions -- Terminology; Wörterbuch